IDEA IMPERIALNA KONFEDERACJI NARODU WOBEC KONCEPCJI FEDERACYJNEJ RZĄDU GEN. WŁADYSŁAWA SIKORSKIEGO - Miszewski, Dariusz (In Gremium. Studies in History, Culture and Politics, 2011)
THE IMPERIAL IDEA OF THE CONFEDERATION OF THE NATION TOWARDS THE FEDERAL CONCEPTION OF THE GOVERNMENT OF GEN. WŁADYSŁAW SIKORSKI The Confederation of the Nation spread the idea of Polish imperialism at the terrain of Middle Europe to eliminate the influence of Germany and USSR. The main terrain of its military and political activities was the eastern lands of the Polish Republic. Poland was supposed to create a Slavic Empire at the Baltic-Black Sea Intermarium by making the Polish western border on the Oder river and the Lusatian Neisse and appointing a Lusatian country, by occupying the Belarusian lands and creating a union with Ukraine in the east, by associating with the Baltic countries in the north and by unions with Bohemia and Slovakia in the south. Together with Great Yugoslavia (union with Bułgaria and Albania) a Middle Europe block would have been formed. Germans and Jews would have been exiled from "the new Poland" and the Ukrainian and Belarusian minorities would have had full cultural and national rights. Poland would have been founded on national and catholic ideals and authoritarian system. The Confederation supported the federal concepts of the Republic of Poland’s government in the Eastern Europe.